OPTIMIZING AGRICULTURAL PRODUCTION THROUGH ORGANIZATIONAL STRATEGIES - Samadov Muhiddin Akhadovich (American Journals, 2024)
Improving the efficiency and productivity of agricultural systems is a critical challenge faced by societies worldwide. This article examines the role of organizational strategies in optimizing agricultural production, drawing on both empirical research and case studies. The study explores the various organizational models, decision-making structures, and management practices that can enhance the performance of agricultural enterprises, from small-scale family farms to large-scale commercial operations. Key factors explored include cooperative and collaborative arrangements, vertical integration, supply chain management, and the integration of digital technologies. The findings provide valuable insights for farmers, agricultural policymakers, and researchers, offering evidence-based recommendations to foster more sustainable and resilient agricultural production systems.
Keywords: Agricultural production, Organizational strategies, Vertical integration, Governance, Organizational culture, Access to resources and technology, Stakeholder engagement, Regulatory and policy environment, Case studies, Evidence-based recommendations